Biased Bullying Victimization and Student Wellbeing: Evidence From a Coarsened Exact Matching Analysis - Kurpiel, Allison (Crime & delinquency, 2025)
This study tested whether bias motivation is an aggravating element of bullying victimization, such that victims of bullying involving bias experience lower wellbeing than victims of nonbiased bullying and nonvictims. Using nationally representative data from the 2009/2010 United States Health Behavior in School-aged Children (HBSC) survey (n = 11,335), I use coarsened exact matching (CEM) to compare wellbeing for youth in exposure and control groups who are similar on the measured covariates. Results reveal that biased bullying is positively associated with unwellness, implying that greater research and policy attention to this form of bullying is warranted.